Initial investigation of marine pollution by oil and grease at Kuala Sg. Perlis, Perlis using the partition gravimetric method / Faridah Hanum Badrun, Zailuddin Ariffin and Baharudin Salleh - Badrun, Faridah Hanum; Ariffin, Zailuddin; Salleh, Baharudin
An initial investigation was carried out to determine the status of marine pollution by oil and grease (O&G) at the jetty area of Kuala Perlis, Perlis. Five sampling points were chosen and the partition-gravimetric method was used to measure the concentration of the O&G pollutant. The results obtained indicated that the waters at the jetty are contaminated by oil and grease, and that tidal conditions affect the measurements due to the decreased boat and ferry activity during low tides. This finding on oil and grease contamination is consistent with results reported by the Department of Environment Malaysia, which indicate the oil and grease levels in the coastal waters off Kedah/Perlis have exceeded the set standard of 0 mg/L.